Increasing inequality in lifetime earnings: A tale of educational upgrading and changing employment patterns - Matthias Seckler (University of Tübingen, Faculty of Economics and Social Sciences, 2019)
This paper provides a detailed decomposition analysis of rising lifetime earnings inequality in Germany using individual employment biographies constructed from high-quality administrative data. The results show that significant parts of rising lifetime earnings inequality among West German men born between the years 1955 and 1974 can be attributed to a lower labor market participation (as a consequence of longer periods of both part-time and non-employment) as well as the educational expansion among later cohorts. The paper also points towards potentially important changes in the penalty linked to employment interruptions, but only finds a moderate impact of skill-biased technological change beyond educational upgrading. The analysis reveals similarities with the development in the U.S. in the sense that the cohorts studied did not only face an increase in inequality, but also a stagnation in earnings for a major part of their career. This trend is even stronger when looking at changes within education groups.
urn:nbn:de:bsz:21-dspace-880900
Keywords: C14; D31; D33; 330; income inequality; lifetime earnings inequality; RIF decomposition